Regulations for access to genetic resources and exportation of weed biocontrol agents in Argentina - McKay, Fernando (2018)
During the last hundred years, plants from Argentina (e.g., water hyacinth and alligator weed) have been accidentally or deliberately transported to other countries where they became invasive weeds. In 1962, the Agriculture Research Service (ARS) of the United States Department of Agriculture established the South American Biological Control Laboratory (SABCL) in Argentina to search and evaluate water weed biocontrol agents. For 50 years, the SABCL contributed to the search and study of 250 natural enemies to control 44 pests in the USA, Africa, Australasia and Europe. In 2003, a more demanding regulatory frame, derived from the Convention on Biological Diversity, was implemented in Argentina. In 2009, the issuing of exportation permits by the Ministry of Environment and Sustainable Development was interrupted, affecting the SABCL’s mission. To resume operations, in 2011, the Argentine government and the ARS negotiated the transformation of the SABCL into the FuEDEI, Fundación para el Estudio de Especies Invasivas. Between 2012 and 2015, FuEDEI exported 14 natural enemies to the USA, Australia, South Africa and Europe. As of 2015, export permits from most Argentine provincial authorities became very hard to obtain. To continue with the exportation of beneficial organisms, FuEDEI acted as liaison to obtain permits from the regulatory agencies of Uruguay, Brazil and Paraguay. At present, there are a few institutions in Argentina conducting weed biocontrol research projects in collaboration with researchers in the USA, New Zealand, Australia, South Africa and Europe. These institutions have joined forces to organize weed biocontrol courses, workshops and online surveys, and to submit weed biocontrol grant proposals to Argentine government funding agencies. We expect these initiatives to raise public visibility of weed biocontrol, revert the ban on organism exchange between Argentina and other countries, and promote research opportunities in Argentina.